Pengaruh Pertumbuhan Penjualan, Intensitas Aset Tetap, dan Risiko Perusahaan Terhadap Penghindaran Pajak: Studi Empiris Pada Perusahaan Sektor Consumer Non-Cyclicals di Bursa Efek Indonesia Tahun 2017 – 2021 - Winda Rizkia; Tri Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research aims to determine the effect of Sales Growth, Fixed Asset Intensity, and Corporate Risk on Tax Avoidance. This type of research is quantitative research with secondary data sources. The population in this research is Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sample selection method used was the Purposive Sampling method so that the samples obtained using this method were 22 out of 98 companies. In this research, descriptive statistical analysis techniques were used, panel data regression model testing, classical assumption testing, and processing program. The results of the research showed that the results of the simultaneous significant test or F test on the variabel Sales Growth, Fixed Asset Intensity, and Corporate Risk have a simultaneous or joint effect on Tax Avoidance. Then, the results of the partial significant test ot t test on the Sales Growth variable have no partial effect on Tax Avoidance. Meanwhile, The Fixed Asset Intensity variable has a partially positive effect on Tax Avoidance and the Corporate Risk variable has a partialyy negative effect on Tax Avoidance.